Probability, statistics, and reliability for engineers and scientists - Ayyub, Bilal M.; McCuen, Richard H. (CRC Press is an imprint of Taylor & Francis, 2011)
Probability, Statistics, and Reliability for Engineers and Scientists, Third Edition introduces the fundamentals of probability, statistics, reliability, and risk methods to engineers and scientists for the purposes of data and uncertainty analysis and modeling in support of decision making